Single VDGA-Based Mixed-Mode Electronically Tunable First-Order Universal Filter - Natchanai Roongmuanpha; Nutcha Likhitkitwoerakul; Masaaki Fukuhara; Worapong Tangsrirat (My University, 2023)
This article presents a mixed-mode electronically tunable first-order universal filter configuration employing only one voltage differencing gain amplifier (VDGA), one capacitor, and one grounded resistor. With the appropriate selection of the input signals, the proposed circuit can realize all three first-order standard filter functions, namely low pass (LP), high pass (HP), and all pass (AP), in all four possible modes, including voltage mode (VM), trans-admittance mode (TAM), current mode (CM), and trans-impedance mode (TIM), from the same circuit structure. It also provides an electronic tuning of the pole frequency and the passband gain by varying transconductance values. Non-ideal and parasitic effect analyses of the proposed circuit were also carried out. PSPICE simulations and experimental findings have both confirmed the performance of the design. A number of simulations and experimental observations confirm the viability of the suggested configuration in practical applications.
Keywords: Passband; Transconductance; Operational transconductance amplifier; All-pass filter; Analog and Mixed-Signal Circuit Design